A case of partial anomalous systemic venous drainage and perioperative detection of cerebral arteriovenous malformations - Nilanjan Dutta; Debasis Das; Raghu Maruti Govindappa; Patralekha Das; Rangan Koley; Manish Kumar Sharma; Amitabha Chattopadhyay; Sanjiban Ghosh (Wolters Kluwer Medknow Publications, 2021)
We report a case of 8-year-old boy with unexplained desaturation and clubbing. Echocardiography showed anomalous drainage of right superior vena cava into left atrium. He did not have any neurological symptoms preoperatively. Some perioperative observations and subtle postoperative behavioral changes prompted us to investigate him further. He was found to have extensive cerebral arteriovenous malformations and hemiatrophy of brain.